Identification and characterization of a plasmid co-harboring blaCTX-M-55 and blaTEM-141 in Escherichia albertii from broiler in China - Weiqi Guo; Di Wang; Xinyu Wang; Zhiyang Wang; Hong Zhu; Jiangang Hu; Beibei Zhang; Jingjing Qi; Mingxing Tian; Yanqing Bao; Na Li; Wanjiang Zhang; et al. (Journal of Integrative Agriculture)
The inappropriate use of cephalosporins lead to the occurrence and global spread of bacteria resistant to these antimicrobials. In this study, we isolated four Escherichia albertii strains from broilers in eastern China. The antimicrobial susceptibility and genomic characterization of these E. albertii isolates were determined. Our results revealed that these four E. albertii isolates exhibited resistance to tetracyclines, chloramphenicol, β-lactams, aminoglycosides, polymyxin B, sulfonamides, quinolones, and other antimicrobials. Among them, EA04 isolate was multidrug resistant and harbored extended-spectrum β-lactamases (ESBL) genes blaCTX-M and blaTEM. Whole genome sequencing and core-genome multilocus sequence typing (cgMLST) based on all ST4638 E. albertii for EA04 inferred highly probable epidemiological links between selected human isolates. Additionally, the ESBL genes blaTEM-141 and blaCTX-M-55 were coexistent in an approximately 75 kb IncFII plasmid pEA04.2 in EA04. Comparative analysis indicated that genes blaTEM-141 and blaCTX-M-55 were located in IS15-blaCTX-M-55-wbuC-blaTEM-141-IS26 region, which similar structures were identified in various bacteria. Furthermore, the plasmid pEA04.2 could be transferable to E. coli EC600 and lead to the resistance to third-generation cephalosporins. These results suggested that chicken potentially serve as a reservoir for multidrug resistant E. albertii, which increases the risk of horizontal transfer of antimicrobial resistance between humans, animals and environment.